Language and “Theory of Mind” development of bilingual and monolingual children in Bulgaria - Kyuchuk, Huseyin S. (Frontiers in Human Neuroscience, 2025)
Children from Bulgaria (N = 120) were tested on language and Theory of Mind (ToM) development. Sixty were ethnic bilingual Turkish children, and 60 were monolingual ethnic Bulgarian children. The age of the children varied between 3;6 to 5;0 years old. Both groups of children in the study were tested in their mother tongues (Turkish and Bulgarian); the Turkish children were also tested in their second language (L2)—Bulgarian, with a language test and Theory of Mind test. Theory of Mind was tested with classical tasks plus a non-verbal ToM task, and the language test comprised measures of wh-complements and evidentiality marking. The hypotheses tested were: H1: The comprehension and production of wh-complements in the mother tongue (L1) at ages 3–6 years will support the understanding of ToM in their second language (L2). H2: Understanding “evidentiality” marking in the mother tongue will support an understanding of false belief ToM tasks in both languages. The results show that the Turkish-speaking children had a lower level of understanding of the classical ToM tasks than the Bulgarian monolingual children, but have equivalent results on the non-verbal ToM task. In the language test, the Turkish-speaking children were better in wh-complements, but weaker in performing the evidentiality test than the Bulgarian monolinguals. The predictors of performance in classic ToM tasks were different from the two ethnic groups: for the Bulgarian monolinguals, performance on the evidentiality test was the best predictor, but for Turkish bilingual children, performance on the low verbal tasks was the only predictor other than age, for both L1 and L2 ToM.